2008
DOI: 10.1002/lt.21494
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the origin of the segment 4 hepatic artery and their clinical implications

Abstract: The threat of ischemic complications following massive resection, especially in living donor hepatectomy or split liver transplantation, has been haunting surgeons for many years. Postmortem dissections of 62 livers were performed to investigate anatomical variations of the principal artery for segment 4 (A4). The origin of A4 was examined separately in the liver with (n ϭ 46) or without (n ϭ 16) an aberrant left hepatic artery (abLHA). A4s were found to be extrahepatic or intrahepatic branches of the right he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 8 publications
2
56
0
2
Order By: Relevance
“…Azoulay et al reported in 2000 that in most cases the MHA originated from the left hepatic artery but could also originate from the RHA, especially in the presence of a replaced LHA 15. In contrast, Jin et al reported in 2008 that the arterial supply to segment IV was mainly via a branch of the RHA or the PHA 16.…”
Section: Discussionmentioning
confidence: 94%
“…Azoulay et al reported in 2000 that in most cases the MHA originated from the left hepatic artery but could also originate from the RHA, especially in the presence of a replaced LHA 15. In contrast, Jin et al reported in 2008 that the arterial supply to segment IV was mainly via a branch of the RHA or the PHA 16.…”
Section: Discussionmentioning
confidence: 94%
“…In 1966, Michels introduced an internationally recognized classification of hepatic arterial variations, in which he described ten types of arterial configuration, based on his observations in 200 autopsy dissections [1]. Later, Hiatt et al introduced a reduced classification with six types, based on a review of operative RHA [7] aRHA [5,6,8] rLHA The segmental arterial vascularization patterns are summarized in this table. The main arterial branches are followed by their segmental territory of vascularization between brackets LHA left hepatic artery, RHA right hepatic artery, MHA middle hepatic artery, aRHA/aLHA accessory RHA/LHA, rRHA/LHA replaced RHA/ LHA a In one patient the rRHA originated from the aorta instead of the SMA reports of 1,000 patients who underwent liver harvesting for orthotopic transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…2). Studies that previously investigated the origin of this arterial branch, often used different definitions, and terms, such as A4 and MHA were interchangeably used [8,12,18]. From an anatomical point of view, the term MHA refers to a hilar artery that originates from the CHA or PHA, between the origins of the LHA and RHA, whereas A4 also can refer to a small intrahepatic branch that originates from the distal LHA or RHA [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La rama segmentaria III nació de la rama izquierda en todos los casos. La rama segmentaria IV nació de la rama izquierda en 50 % y de la derecha en 20 % variación descrita también por Jin et al (2008). Panagouli et al (2011) reportaron que las arterias hepáticas accesorias pueden nacer de la gástrica izquierda o la mesentérica superior, para ambos lados, solo el ingreso a su territorio correspondiente las numera y clasifica.…”
Section: Discussionunclassified